A construção de uma nova ordem: análise da interventoria de Rui Carneiro no estado da Paraíba (1940-1945) - Silva, Jean Patrício da (2013)
This study aims to identify the main actions of the period of the New State in Paraíba, in particular, the period of the Ruy Carneiro s Government, between 1940-1945. Thus, it will seek to analyze the process of centralization of the state and the bureaucratic reform - administrative, from the perspective of power relations established after the coup movement entitled "New State" of 1937. This study contributes to the local historiography citing the relations between this reform in the state apparatus in accordance with the programmatic line of action of the Government. The few studies that underlie the period 1940-1945 do not address in a systematic way the Government of Ruy Carneiro. Overall, what is known about this period, in the state of Paraíba, the news came only in the newspapers of the time and documents, reports, decrees or small texts with specific themes. As a contribution to the local historiography, this research seeks to delve into research on local governments Vargas period, specifically the Ruy Carneiro s Government.